Pengaruh Praktik Environment, Social, Governance (ESG) terhadap Nilai Perusahaan dengan Peran Moderasi Media Exposure - Raisa Amalia Salsabila; Idrianita Anis (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) practices on firm value, with media exposure as a moderating variable. The research employs a quantitative approach using secondary data obtained from annual reports, sustainability reports, and corporate publications of infrastructure companies listed on the main board of the Indonesia Stock Exchange (IDX) during the 2018–2024 period. Firm value is measured using Tobin’s Q, while ESG practices are assessed based on the Triple I Framework, which consists of Intention, Integration, and Implementation. Media exposure is measured through a scoring of positive ESG-related news coverage. The sample comprises 24 companies with a total of 154 observations. Data analysis is conducted using panel data regression with a Fixed Effect Model and Moderated Regression Analysis. The results indicate that ESG practices have a positive and significant effect on firm value. However, media exposure does not have a significant effect on firm value and fails to moderate the relationship between ESG practices and firm value. These findings suggest that firm value is more strongly influenced by the quality and consistency of ESG implementation rather than media intensity, implying that ESG should be viewed as a long-term business strategy rather than merely a communication tool.